Internet of Things (IOT) Development for The Chicken Coop Temperature and Humidity Monitoring System Based on Fuzzy - Jamaluddin Husein; Oktaf Brillian Kharisma (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The high increase in broiler each year there are several factors that must be considered, one of them is the temperature and humidity of the cage. The brooding cage space of 10 ekor/1. If more then that couse broiler is not optimal. The temperatur needed is 29°C-35°C and humidity 60%-70% for brooding. In general control of temperature and humidity, unable to maintain cage needs. Then it is necessary to do automatic control using the fuzzy logic method and the concept of Internet of Things (IoT). Base on the testing result the system has been able to maintain the set point of temperature and humidity and get broiler growth not same, The best stability value during the test is condition without DOC produces no overshoot temperature parameters and steady state error 0,48, no overshoot and steady state for humidity. On the condition with DOC produces overshoot temperature 0,06 and steady state error 0,15, and overshoot 0,1 and steady state 0,4 for humidity. While on the IoT concept has been able to display the temperature and humidity values on the cage